Erythema Nodosum following Nocardia Infection: A Case Report - Sujing Li; Bingzhou Ji; Yan Teng; Hui Tang; Hong Cui; Xiaohua Tao; Yibin Fan; Youming Huang (Medicina, 2022)
Cutaneous nocardiosis is a rare bacterial infection that can result in various dermatologic manifestations such as actinomycetoma, lymphocutaneous infection, superficial skin infection, and secondary infection due to hematogenous dissemination. We report on a Chinese patient with erythema nodosum-like exanthema, possibly secondary to nocardiosis. Our diagnosis for this patient was based on the clinical presentation, histopathological evidence, and microbiological findings. Given the protean manifestation of Nocardia, persistent reports on new presentations of the disease are important for early identification and treatment.